Berlin, Ontario, in the Age of the ABC - Lucas, Jack (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2013)
Between 1890 and 1910, the town of Berlin, Ontario, adopted special-purpose bodies, such as water commissions and park boards, with enthusiasm. Why did Berlin’s civic leaders respond to these institutions so enthusiastically? This paper suggests that internal diffusion, fuelled by an argument about municipal capacity, was at work in Berlin at the time. The paper also critically examines two alternative explanations for the town’s enthusiasm, one grounded in Wilsonian reform, and the other in elite self-insulation.